Etude probiotique des bactéries lactiques isolées à partir de Hamoum (blé fermenté) - HAMMOUM, Saliha Namira (My University, 2017)
The lactic acid bacteria are used as bacteria with probiotic potential, the latter must face the gastrointestinal stress in order to bring their beneficial effects to the sites of action. Indeed, ingested bacteria must survive the acidity of the stomach and the presence of bile salts to express their specific metabolic functions. The aim of this project is to study the resistance of lactic bacteria to gastrointestinal stress. Therefore, two strains isolated from Hamoum BL8 Lactobacillus and M5 Pediococcus were studied during our practice. The latter two were exposed to one of the various stresses that are the objects of a primary obstacle in the digestive tract. We tested the sensitivity of our lactic strains to the particular conditions found in the stomach and intestine acidity pH (2.5, 4.5 and 6.5) and the presence of bile salts at different pH: 2 , 5 and 6.5 (0.3, 0.5% and 1%). According to the results, the strains were resistant to low pH (2.5), which had a bacteriostatic effect, or M5 had the highest viability percentage relative to BL8. The strains also resisted bile salts. On the other hand, we studied the susceptibility of lactic strains to antibiotics, the results of which demonstrated remarkable resistance to some antibiotics used. In order to evaluate the biotechnological importance of our strains, we evaluated their acidifying power. The values recorded express a good acidifying power for the two lactic strains.
Keywords: Probiotics; lactic strains; bile salt; acidity; resistance; Hamoum; الحموم; حموضة المقاومة; ملح الصفراء; البروبيوتيك; سلالات اللبنية; Probiotiques; souches lactiques; sel biliaire; acidité; résistance; Hamoum